ENDOTHELINES AND CARDIOVASCULAR PATHOLOGY - A. M. Alieva; N. N. Chirkova; T. V. Pinchuk; O. N. Andreeva; V. Yu. Pivovarov (Российский кардиологический журнал)
Many studies of the last years were concerned the changes in endotheline system as one of the chains in endothelial dysfunction. Activation of endotheline system, which is marked by the increase of endotheline level and its predecessor, is common for many cardiovascular diseases. The significant increase of endotheline-1 and Big-endotheline is shown in atherosclerosis, angina, acute myocardial infarction, hypertensive disease and pulmonary hypertension.